Inuit Subsistence, Social Economy and Food Security in Clyde River, Nunavut - Harder, Miriam T.; Wenzel, George W. (ARCTIC, 2012)
This paper examines the flow of money and country food resources within an Inuit extended family (ilagiit) in Clyde River, Nunavut, to understand the effects of a mixed wage-income and hunting economy on customary resource sharing and food security. Over a 12-week period in 2009, data were gathered through participant observation and bi-weekly recall interviews with 10 ilagiit households in the community. The findings are compared to data on sharing collected in 1999 from the same family group. Results indicate that resource sharing, especially for country food, continues to follow traditional kinship patterns and retains considerable importance in the group’s aggregated “income.” Further, imported foods are shared, but on what appears to be an ad hoc basis, while control of money appears to rest with individuals. Overall, differences between households in cash income, seen in terms of hunting and fishing equipment, are more apparent in 2009 than in 1999, but this inequality is moderated by shared use among close kin of large items like freighter canoes and outboard motors. At this time, social relations critically buffer subsistence disparities between lower- and higher-income households in culturally prescribed ways. Our study of the socioeconomic dynamics within an Arctic community is particularly valuable for informing a culturally relevant understanding of Arctic food security, given significant recent interest in this research area. Le présent article se penche sur le flux monétaire et les ressources alimentaires prélevées dans la nature au sein d’une famille inuite étendue (ilagiit) de Clyde River, au Nunavut, dans le but de comprendre la dynamique d’un revenu mixte et d’une économie basée sur la chasse en matière de partage des ressources coutumières et de salubrité des aliments. Sur une période de 12 semaines en 2009, des données ont été recueillies par le biais d’observations des participants et d’entrevues de rappel aux deux semaines auprès de 10 foyers ilagiit faisant partie de la collectivité. Les ...